Tinjauan literatur sistematis: Dampak inisiasi menyusui dini (IMD) terhadap pola menyusui dan kesehatan bayi - Audry Maharani Agustine Putri; Anita Rahmiwati; Haerawati Idris (Poltekkes Kemenkes Aceh, 2026)
Background: Breast milk is the main source of nutrition for infants, and early initiation of breastfeeding within the first hour after birth plays an important role in supporting the success of exclusive breastfeeding. Despite being recommended by the World Health Organization, early initiation of breastfeeding (EIB) coverage in Indonesia remains low. The 2023 Indonesian Health Survey noted that only 45.1% of infants received EIB, which is influenced by a lack of education, medical interventions during delivery, and unsupportive health facility policies. This highlights the importance of further examining the impact of IMD on breastfeeding success and overall infant health.Objectives: This article aims to to explore the impact of EIBF on breastfeeding patterns and infant health.Methods: This study is a literature review that uses a systematic approach with searches on Google Scholar and the PubMed database using the keywords ‘early initiation of breastfeeding’, ‘exclusive breastfeeding’, and ‘breastfeeding patterns’ (2020–2025). Article selection followed the PRISMA guidelines, starting with identification of 550 initial articles, followed by screening based on tittles and abstracts, resulting in 258 articles. The eligibility evaluation stage excluded 66 articles that could not be included in the criteria, resulting in six final articles for review. Results: Early initiation of breastfeeding is important for the success of exclusive breastfeeding and infant health. EIB increases maternal confidence, reduces early interventions, such as the use of formula, and stimulates the suckling reflex during the sensitive first 2 hours after birth. In addition, EIB supports milk production through the stimulation of the hormones prolactin and oxytocin. Skin contact during EIB helps maintain the baby's body temperature and prevents hypothermia. In addition to these physiological benefits, EIB strengthens the emotional bond between mothers and babies, which contributes to the long-term success of breastfeeding.Conclusion: EIBF provides significant benefits for infant health and development while supporting successful breastfeeding.